Mixed Nonseminomatous Germ Cell Tumor with Rhabdomyosarcomatous Malignant Transformation in a Pediatric Patient - Pham, Robin L; Ray, Anish; Margraf, Linda R (Indian Journal of Medical and Paediatric Oncology, 2018)
Testicular germ cell tumors (GCTs) are the most common malignancy in males aged 15–34. The transformation of GCTs into secondary somatic-type malignancies is rare, and the lack of clear treatment guidelines presents a clinical challenge for treating physicians, especially when chemosensitivities do not overlap. We present the case of a 15-year-old-male with a mixed nonseminomatous malignant GCT with an embryonal rhabdomyosarcoma component, which made up 60% of the primary tumor. He was successfully treated with surgical resection and chemotherapy. We highlight our experience in diagnosing and treating this tumor, and through literature review, suggest treatment guidelines for treating a pediatric patient with similar tumor presentation.
Keywords: Pediatrics; rhabdomyosarcoma; secondary somatic-type malignancy; testicular germ cell tumor